Nanofibrous Online Solid-Phase Extraction Coupled with Liquid Chromatography for the Determination of Neonicotinoid Pesticides in River Waters - Šrámková, Ivana H; Horstkotte, Burkhard; Carbonell-Rozas, Laura; Erben, Jakub; Chvojka, Jiří; Lara, Francisco J; García-Campaña, Ana M; Šatínský, Dalibor (Membranes, 2022)
Polymeric nano- and microfibers were tested as potential sorbents for the extraction of five neonicotinoids from natural waters. Nanofibrous mats were prepared from polycaprolactone, polyvinylidene fluoride, polystyrene, polyamide 6, polyacrylonitrile, and polyimide, as well as microfibers of polyethylene, a polycaprolactone nano- and microfiber conjugate, and polycaprolactone microfibers combined with polyvinylidene fluoride nanofibers. Polyimide nanofibers were selected as the most suitable sorbent for these analytes and the matrix. A Lab-In-Syringe system enabled automated preconcentration via online SPE of large sample volumes at low pressure with analyte separation by HPLC. Several mat layers were housed in a solvent filter holder integrated into the injection loop of an HPLC system. After loading 2 mL sample on the sorbent, the mobile phase eluted the retained analytes onto the chromatographic column. Extraction efficiencies of 68.8-83.4% were achieved. Large preconcentration factors ranging from 70 to 82 allowed reaching LOD and LOQ values of 0.4 to 1.7 and 1.2 to 5.5 µg·L-1, respectively. Analyte recoveries from spiked river waters ranged from 53.8% to 113.3% at the 5 µg·L-1 level and from 62.8% to 119.8% at the 20 µg·L-1 level. The developed methodology proved suitable for the determination of thiamethoxam, clothianidin, imidacloprid, and thiacloprid, whereas matrix peak overlapping inhibited quantification of acetamiprid.
Keywords: neonicotinoids; nanofibers; membrane preconcentration; online SPE; Lab-In-Syringe